...And Lucy liked it! : laureates HISK 2005 - HISK, Antwerpen (Antwerpen : Hoger Instituut voor Schone Kunsten, HISK, 2005)
Czerepok, Hubert; de Boer, Karel Pieter; De Leener, Eva; De Vries, Erki; Dheedene, Stefaan; Eussen, Anneke; Geeraert, Peter; Gruijthuijsen, Krist; Kerremans, Eva; Lybeer, Charlotte; Marit, Liesbeth; Mathysen, Pieter; Meessen, Vincent; Meuris, Wesley; Noël, Cédric; Noirfalise, Christian; Nollet, Lien; Provost, Nicolas; Roncada, Arno; Van Nechel, Kris; Woestenborghs, Tom
Graduation exhibition, 03.12.2005 - 18.12.2005
Engels, Nederlands
boek